PENINGKATAN KINERJA PEGAWAI BERDASARKAN KEPEMIMPINAN, DAN MOTIVASI KERJA MELALUI KEPUASAN KERJA : STUDI PADA PEGAWAI TETAP DAN NON-PIMPINAN PT. KIE INDONESIA - Rahmah Syakbaniah; Santi Rimadias (Ibs Press, 2024)
This research aims to find out what factors influence employee performance, and researchers also want to know how much influence the independent variables influence employee performance, namely leadership and work motivation, through job satisfaction. The sample for this research is permanent employees (non-leaders) of PT. KIE Indonesia (Kumon) totalling 50 people. This research uses a quantitative research design carried out through interviews and questionnaires in data collection. In this research, data collection was carried out over a period of 36 days starting from 24 June 2023 to 29 July 2023. The supporting application used as a tool to calculate data for this research was using SmartPLS 4.0 software. The research results show that there is a positive influence between leadership on two variables, namely work motivation and job satisfaction, then work motivation has an influence on two variables, namely job satisfaction and employee performance, work motivation also has an influence on employee performance through job satisfaction. However, this research also shows that leadership has no effect on employee performance, and it has also been proven that leadership has no effect on employee performance through job satisfaction. Suggestions for further research are expected to be able to examine a wider range of objects, and not only at PT. These include work discipline, competence, and organizational culture.